NiTi materials : biomedical applications - Oshida, Yoshiki; Tominaga, Toshihiko (De Gruyter STEM., 2020)
Nickel-Titanium alloys are smart materials exhibiting unique properties such as superelasticity and shape-memory effect. The material has been used as orthodontic wires in the dental field for over 20 years. This book is a comprehensive overview to the field of Ni-Ti Materials and the physical, chemical and mechanical properties of this versatile alloy. In addition, complications and challenges exhibited in applications are also discussed.